Bugs: a close-up view of the insect world - Maynard, Christopher (Dorling Kindersley London, 2001)
Contains facts and figures on a wide range of insects from the gross to the everyday, describing what bugs or insects are, their body structure, habits, environment, and why they are or are not beneficial to man